Nepal and China Trade Relations (Voice: A Biannual & Bilingual Journal, 2023)
Because landlocked countries can only access sea ports through neighbors, their economies are heavily influenced by them. A nation’s economy will grow slowly without strong trade. A country must have solid diplomatic relations with its neighbors in a globalizing globe. Many studies have examined commerce with India, but few with China. The Nepal-China commercial relationship is the topic of this study. From the 5th century to present, Nepal and China have cooperated. This relationship has grown. This report examines Nepal-China trade opportunities and difficulties. Trade connections and import-export trade between these countries are the focus of this study. The analysis covers 2007/08 to 2016/17 trade volumes between these countries. The trade imbalance expanded from 228 million to 1 billion between 2007/08 to 2016/17, highlighting the significant difference between countries. The findings show Nepal has significant trade potential in agriculture, hydroelectricity, and banking sectors, but its economy, infrastructure, and political instability provide hurdles. Nepal is paving the path to prosperity with new trade agreements and existing and proposed activities with China.